Group Communication In Arranged Marriages In The Nurul Islam Islamic Boarding School Family in Jember : Komunikasi Kelompok Dalam Perjodohan Di Kalangan Pesantren Nurul Islam Jember - Najmah, Najmah; Juariyah, Juariyah (Universitas Muhammadiyah Sidoarjo, 2025)
The phenomenon of arranged marriage is a phase which becomes a moment or form of determining a partner for future offspring, and arranged marriages within the families of Kiai Pesantren Nurul Islam Jember is a phenomenon that occurs to this day. Matchmaking at the Nuris Jember Islamic Boarding School is democratic as they are given the right to accept or reject the match. In connection with this problem, the researcher aims to examine how group communication occurs in matchmaking at the Nurul Islam Islamic Boarding School in Jember. The research method used is a qualitative research method. The data analysis technique is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of this research are first, in the process of choosing a mate for their sons and daughters there are two stages, first, Kyai as parents prefer and prioritize the Kyai's descendants/native factors, and second, matchmaking is carried out outside the Nuris family which cannot be separated from several factors. certain. Second, so that the Islamic boarding school's struggle continues and the creation of family ties with other Kyai and arranged marriages in the Nuris Islamic Boarding School as well as to avoid difficulties that will hinder it in the future. Third, form a family that is sakinah, mawaddah, wa rahmah, full of love and always gets God's grace. In this case, the families of the arranged marriage can be of the same understanding and unity in carrying out and building family life.